The shadow lines - Ghosh, Amitav, 1956- (Ravi Dayal, 1998)
It starts with the boy's eccentric cousin Tridib, who gives him worlds to travel in and eyes to see them with long before he leaves Calcutta. His beautiful cousin lla, who would always break his heart, has been all around the world and seen nothing; while in his imagination he touches the great pyramid,she remembers the inconvenient location of the 'Ladies' at Cairo Airport. But this is part of her irresistible charm. As the boy grows he find himself sucked into history: his old grandmother stuck in a family feud; the relationship with England that took Tridib and his parent to London; their English friends, whose daughter's love for Tridib can only end in tragedy. Out of an intricate web of memories, relationships and images Amitav Ghosh builds a vivid and moving story. Its focus is the meaning of political freedom and the force of nationalism, the Shadow line between people and Nations-- which is the source of terrifying violence